Inhibitory effects of tanshinones towards the catalytic activity of UDP-glucuronosyltransferases (UGTs) - Xu-Xin Zhang; Yun-Feng Cao; Li-Xuan Wang; Xiao-Lin Yuan; Zhong-Ze Fang (Taylor & Francis Group, 2017)
Contents: Danshen is a popular herb employed to treat cardiovascular and cerebrovascular diseases worldwide. Danshen-drug interaction has not been well studied. Objective: The inhibitory effects of four major tanshinones (tanshinone I, tanshinone IIA, cryptotanshinone, and dihydrotanshinone I) on UDP-glucuronosyltransferases (UGTs) isoforms were determined to better understand the mechanism of danshen-prescription drugs interaction. Materials and methods: In vitro recombinant UGTs-catalyzed 4-methylumbelliferone (4-MU) glucuronidation reaction was employed. Tanshinones (100 μM) was used to perform the initial screening of inhibition capability. High-performance liquid chromatography (HPLC) was used to separate 4-MU and its glucuronide. In vitro-in vivo extrapolation (IV-IVE) was employed to predict in vivo inhibition situation. Results: Cryptotanshinone inhibited UGT1A7 and UGT1A9 with IC50 values of 1.91 ± 0.27 and 0.27 ± 0.03 μM, respectively. Dihydrotanshinone I inhibited UGT1A9-catalyzed 4-MU glucuronidation reaction with the IC50 value of 0.72 ± 0.04 μM. The inhibition of cryptotanshinone towards UGT1A7 and UGT1A9 was best fit to competitive inhibition type, and UGT1A9 was non-competitively inhibited by dihydrotanshinone I. Using in vitro inhibition kinetic parameters (Ki) and in vivo maximum plasma concentration (Cmax) of cryptotanshinone and dihydrotanshinone I, the change of area-under-the-concentration-time curve (AUC) was predicted to be 0.4-4.2%, 3.7-56.3%, and 0.6-6.4% induced by cryptotanshinone and dihydrotanshinone inhibition towards UGT1A7 and UGT1A9, respectively. Discussion and conclusion: The inhibitory effects of tanshinones towards important UGT isoforms were evaluated in the present study, which provide helpful information for exploring the mechanism of danshen-clinical drugs interaction.